KEANDALAN SISTEM INTRUMENTASI PLTG DI PT. PLN TELUK LEMBU PEKANBARU - Poppy Dewi Lestari; Rino Eldika (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
PT. PLN PLTD / G Teluk Lembu is one company engaged in power generation, which in its operations using equipment that has been integrated with each other and have a system of instrumentation for each controller. Great ability of this instrumentation was also followed by the risk of loss of power in the event of failure of electricity distribution. This is certainly not desired by PT. PLN, because of the failure resulted in loss of income and opportunity. Therefore PT. PLN implement instrumentation system on Power Plant Gas (PLTG) that can provide controlled so as to boost the reliability.                Reliability is one important performance parameter for the reliability prediction results can be used to determine the choice to use an instrumentation and its implementation at a power plant . Reliability parameters of a generator includes the availability (availability), system downtime and Mean Time To Failure (MTTF) or the lifetime prediction of a network. By analyzing the above parameters obtained power plant instrumentation system availability levels in the PT. PLN PLTD / G Teluk Lembu is greater than 99.99%. Level of availability (availability) has gained an average of 99.99873259%, with a value of 6.66150696 system downtime minutes per year, and Mean Time To Failure (MTTF) is 69.98554999 years.                With the calculation results in It can be concluded that the power plant instrumentation system on PT. PLN to meet the requirements that have been standardized for industrial processes. Key Words: Availability, Down Time System, Instrumentation PLTG, reliability  and MTTF